Traumatic Racial Encounters in Toni Morrison's God Help the Child (Journal of Bhuwanishankar, 2022)
This study examines the cultural trauma of characters with a cultural embodiment of race in the sophisticated but claustrophobic contemporary American society. Morrison's God Help the Child (2015) projects pain and trauma that live under the colored skin as a part of the author's and her character Bride's immense suppression of desire as a triggering force to past memories. Further, this research explores how traces of slavery in the past reconstitute trauma and how the interplay between dominant and residual cultures shapes the trauma of the African Americans. Morrison reveals the inter-racial and intra-racial conflicts in new generations of Americans by presenting the traumatic mind of her protagonist Bride who reconfigures traumatic history through critical acting out and working through trauma. Eventually, she succeeds in recovering and turning her grief into strength. The way through which such trauma is coped with is a researchable issue. It unfolds an individual's consciousness of racism and its influence on the individual psyche as a part of cultural trauma. Further, it unveils the inter-racial and intra-racial consciousness among the African Americans as they develop some guilt complexes within themselves due to their double consciousness and ambiguity contrary to social values. This is an internal conflict experienced by them in an oppressive society.